Pengaruh Pemberian Campuran Eceng Gondok Tetes dan Urea Terhadap Pertambahan Berat Badan Anak Sapi Aceh Jantan - Mahyuddin Mahyuddin (Jurnal Agripet, 2001)
ABSTRACT.The experiment was conducted in Experimental Farm of Agriculture Fakulty, Syiah Kuala University. The purpose of the experiment was to study the effect of mixed Water hyiacinth molasses and urea fed on live-weight gains of Aceh Bullocks. Four Aceh Bullocks (live weight: 140-170 kg, age : 12 months) were used design was Latin Square which were divided into treatments and 4 periods. The treatments were : 0 percent (A), 15 percent (B), 30 percent (C) and 45 percent (D). Water hyiacinth. The resulth of this experiment showed that no significant differences on feed consumption and live weight gains. However, among the treatments, feed consumption of treatment 45 percent tends to decrease. On the other hand, live-weight gains Aceh Bullocks of treatment 45 percent tends to increase. There was a significant difference on feed conversion. Feed conversion of treatment 45 percent is the best.